Conditioned taste aversion and Ca/calmodulin-dependent kinase II in the parabrachial nucleus of rats - Krivanek, J (Neurobiology of learning and memory, 2001)
Bielavska and colleagues (Bielavska, Sacchetti, Baldi, & Tassoni, 1999) have recently shown that KN-62, an inhibitor of calcium/calmodulin-dependent kinase II (CaCMK), induces conditioned taste aversion (CTA) when introduced into the parabrachial nucleus (PBN) of rats. The aim of the present report was to assess whether activity of CaCMK in the PBN is changed during CTA. We induced CTA in one group of rats by pairing saccharin consumption with an ip injection of lithium chloride. Another group of rats received lithium alone (without being paired with saccharin consumption) to test whether lithium has an effect on CaCMK in the PBN, independent of those effects due to training. In animals receiving CTA training, CaCMK activity in extracts of PBN was reduced by approximately 30% at the postacquisition intervals of 12, 24, and 48 h, compared to control animals receiving saccharin with saline injection. By 120 h after CTA training, no effect on CaCMK was present. At those postacquisition intervals showing CaCMK activity effects due to CTA, there were no effects attributable to lithium alone. Lithium alone produced only a short-lasting reduction in CaCMK activity (at 20 min a 30% decrease, at 60 min a 23% decrease; and at 6, 12, and 24 h no decrease). The time course of lithium-induced effects differed markedly from that of CTA training. All changes were Ca2+/- -dependent; we did not observe any changes in Ca-independent activity. CTA effects on CaCMK were selective for PBN, insofar as we did not observe any CTA effects on CaCMK in the visual cortex, a brain region unrelated to taste pathways. Since CTA produces a relatively long-lasting reduction in CaCMK activity (lasting 2 days or more) specifically in the PBN, which is critical a relay for taste information, the reduction of CaCMK activity may enable the consolidation of taste memory in an aversive situation.
Keywords: plexus brachialis; Calcium; Rats, Long-Evans; potkani Long-Evans; Conditioning, Psychological; Rats; podmiňování (psychologie); vápník; Calcium-Calmodulin-Dependent Protein Kinases; Taste; chuť; Animals; krysa rodu Rattus; mužské pohlaví; Male; Brachial Plexus; zvířata; proteinkinasy závislé na vápníku a kalmodulinu